CARRYING ANGLE AND ITS CO-RELATION WITH DIFFERENT PARAMETERS HEIGHT, LENGTH OF FOREARM, AND AGE (International Journal of Physiotherapy, 2020)
Background: The carrying angle is known as the acute angle created by the arm's median axis and that of the forearm, which is completely extended & supinated, and thus measures the forearm's lateral obliquity. This angle is best observed when the forearm is in full extension, elbow in supination, and the external rotation of the shoulder. The purpose of the research is to study the co-relationship between carrying angle and various parameters of height, forearm length, and age.Methods: A total of 106 asymptomatic, healthy students were selected from 18-22 years of age at Ravi Nair Physiotherapy College, DMIMS, Sawangi Meghe, Wardha. The carrying angle was measured with a goniometer. A measuring tape was used to measure the overall height of the subject and length of the subject's forearm.Results: The p-value was found p< 0.05 on comparing carrying angle with height and forearm length, which suggests significant co-relation. Thus the person's height is inversely related to the carrying angle. The forearm length & height are directly related to each other; hence the forearm length is also related to the carrying angle. The p-value was found p > 0.05 on comparing carrying angle with age, which is non-significant. Thus there is no significant variation in carrying with age since the subjects were within a limited age range.Conclusion: The carrying angle depends on the bone's length in the forearm. If the bone length is significantly greater, the angulation of the proximal articulation of the proximal articular surface is lower, hence the carrying angle is lower and vice versa.